Effects of the supplemental chromium form on performance and oxidative stress in broilers exposed to heat stress - Şahin, Nurhan; Hayirli, A.; Orhan, C.; Tuzcu, M.; Akdemir, F.; Komorowski, J. R.; Şahin, Kazım (Elsevier, 2017)
This experiment was conducted to investigate effects of the organic complex form of supplemental chromium (Cr) on performance, oxidative stress markers, and serum profile in broilers exposed to heat stress (HS). A total of 1,200 10-day-old boilers (Ross-308) was divided into one of the 6 treatments (2 environmental temperatures x 3 diets with different Cr forms). The birds were kept in temperature-controlled rooms at either 22 +/- 2A degrees C 24 h/d (thermoneutral, TN group) or 34 +/- 2A degrees C for 8 h/d, 08:00 to 17:00 h, followed by 22A degrees C for 16 h (HS group) and fed either a basal diet (C) or the basal diet supplemented with Cr (200 mu g/kg) through 1.600 mg of CrPic (12.43% Cr) and 0.788 mg of CrHis (25.22% Cr). Feed intake and body weight were recorded weekly. After cervical dislocation, liver samples were harvested to analyze Cr concentration and glucose transporter-2,4 (GLUT-2,4) expression. The breast meat also was sampled for the concentration of Cr and expressions of nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor kappa B (NF-kappa B). Data were analyzed by 2-way ANOVA. Heat stress caused depressions in feed intake (12.1%) and weight gain (21.1%) as well as elevations in feed conversion (11.2%) and abdominal fat (32.8%). It was also associated with depletion of Cr reserves and increases in serum concentrations of glucose, cholesterol, creatine, and enzymes. Exposure to HS was accompanied by suppression of the expressions of Nrf2 and GLUT-2 in muscle and GLUT-4 in the liver and amplification of the expression of NF-kappa B in muscle. Both Cr sources partially alleviated detrimental effects of HS on performance and metabolic profile. The efficacy of Cr as CrHis was more notable than Cr as CrPic, which could be attributed to higher bioavailability. In conclusion, CrHis can be added into the diet of broilers during hot seasons to overcome deteriorations in performance and wellbeing related to oxidative stress.
Keywords: broiler; chromium-histidinate; chromium-picolinate; heat stress